Defining Justice and Dignity Through Gendered Peace Building: A Case Study of Gender-Based Violence During Armed Conflict in Nepal - Risal, Susan (Social Inquiry: Journal of Social Science Research, 2020)
The prolonged transition and the long awaited journey for justice for a decade has led to increased anger and frustration among women who survived gendered violence during the Nepali armed conflict (1996-2006). During April 2017-May 2018, a case study fieldwork was conducted with women who survived conflict-related sexual violence during the armed conflict in Nepal. Using a critical theory framework and case study methodology, this research sought to understand how the women who faced gender based violence during the conflict era of Nepal define dignity and justice from their own lived experience and consequently, their needs for reparations. Ultimately, with resulting interventions by presenting these women’s voices and needs to the truth seeking commissions, other government bodies, and national and international organizations working with conflict affected women, women’s quest for dignity, justice and needs could be addressed. The findings of this study have also expanded the body of knowledge and best practices for reconciliation in contexts where gender based violence has been used as a weapon of war.